A detailed account of the reproductive strategy and developmental stages of Nasikabatrachus sahyadrensis (Anura: Nasikabatrachidae), the only extant member of an archaic frog lineage - Zachariah, Anil; Abraham, Robin Kurian; Das, Sandeep; Jayan, K. C.; Altig, Ronald (Zootaxa, 2012)
Novel and significant data on the breeding biology and tadpole morphology of Nasikabatrachus sahyadrensis expands ourunderstanding of this unusual frog and clarifies some data in other reports. Nonpigmented eggs are laid in arrays or clumpsin small shaded rocky pools in the bedrock of torrential streams, as they are charged by early monsoon rains. The suctorialtadpole adapted to rheophilic habitats, has a strongly depressed body, dorsal eyes, complete marginal papillae, a labialtooth row formula of 2/3 or 2/3(1), and a medial vent with unusual flaps subtending the vent and limb buds. Tadpoles meta-morphose in about 100 days. Additional site records and issues relating to the conservation of this frog and its habitat in the southern Western Ghats of India are discussed.